Confronting needlestick and sharp injuries in healthcare: a decade of struggle and progress in a university teaching hospital - Shuk-Ching Wong; Lithia Lai-Ha Yuen; Germaine Kit-Ming Lam; Monica Oi-Tung Kwok; Crystal Yuen-Ki Siu; Bella Hong-Yan Li; Jonathan Hon-Kwan Chen; Simon Yung-Chun So; Kelvin Hei-Yeung Chiu; Vincent Chi-Chung Cheng (BMC Health Services Research, 2025)
Abstract Background Needlestick and sharp injuries (NSIs) among healthcare workers (HCWs) are a significant concern in infection prevention. This study analyzes the incidence and characteristics of NSIs at Queen Mary Hospital and assesses the effectiveness of targeted training programs for interns. Methods A retrospective analysis was conducted on NSI reports from 2014 to 2023, focusing on episodes involving medical, nursing, allied health, and other staff. Personal coaching training programs for newly recruited interns were implemented in 2019 to enhance safety practices. NSI episodes were analyzed in relation to patient days and full-time equivalents (FTE). Results During the study period, there was a mean of 464,118 patient days per year, with an average of 5,928 HCWs per year. A total of 1,076 NSI episodes were reported, resulting in a mean of 2.31 episodes per 10,000 patient days and 1.82 episodes per 100 FTE. Medical staff accounted for 502 episodes (47%), while nursing staff had 339 episodes (32%). The mean NSI episodes among medical staff were significantly higher than nursing staff per year, measured per 10,000 patient days (1.08 ± 0.21 vs. 0.73 ± 0.16, p = 0.001) and per 100 FTE (8.46 ± 1.95 vs. 1.62 ± 0.40, p < 0.001). Of the 1,076 episodes, 430 (40%) occurred in HCWs with less than 1 year of experience, with 278 (65%) attributed to interns, contributing to 26% of the overall NSI burden. Most incidents among interns occurred in wards (95%, 264/278), with 95% (252/264) involving hollow needles. Notably, 54% (149/278) involved safety-equipped devices, yet 94% (140/149) of these were not activated properly. Following targeted training, NSI rates among interns significantly decreased from 0.82 to 0.46 per 10,000 patient days (R2 = 0.977, p = 0.001) and from 6.84 to 3.40 per 100 FTE (R2 = 0.874, p = 0.020) from 2019 to 2023. Conclusions The study highlights the ongoing issue of NSIs among HCWs, especially inexperienced interns. While training programs have shown promise in reducing NSI rates, the high incidence of safety devices not being effectively utilized underscores the need for continuous education and hands-on training to enhance safety practices and prevent NSIs in healthcare settings.